Mengapa pelanggan membeli produk secara online? Efek dari content marketing, online review, dan brand image - Azizah, Rezekila; Riki, Riki (Bahtera Inovasi, 2025)
This study aims to conduct research on how Content Marketing, Online Reviews, and Brand Image influence purchasing decisions for Wardah skincare products for people in Batam City. dnerm The research population includes Batam people who have purchased Wardah skincare products online, with a sample size of 170 respondents. The method used is a quantitative approach, where data is collected through a survey using a questionnaire distributed to the people of Batam according to predetermined criteria. Data analysis was performed with SEM (Structural Equation Model) using SmartPLS software. The findings of this study indicate that Online Reviews have no influence on purchasing decisions, while Content Marketing and Brand Image are proven to have a significant effect on purchasing decisions. In addition, the people of Batam are very concerned about Content Marketing and Online Review when assessing a skincare brand.